2021
DOI: 10.1038/s41598-021-84495-0
|View full text |Cite
|
Sign up to set email alerts
|

Smart optical cross dipole nanoantenna with multibeam pattern

Abstract: In this paper, an optical smart multibeam cross dipole nano-antenna has been proposed by combining the absorption characteristic of graphene and applying different arrangements of directors. By introducing a cross dipole nano-antenna with two V-shaped coupled elements, the maximum directivity of 8.79 dBi has been obtained for unidirectional radiation pattern. Also, by applying various arrangements of circular sectors as director, different types of radiation pattern such as bi- and quad-directional have been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Recently, multi-beam reconfigurable plasmonic nano-antennas based on graphene have attracted tremendous attention due to the unique features of graphene as a promising two-dimensional (2D) monoatomic layer of carbon atoms in optical and terahertz (THz) frequency range for electronic and photonic applications [3,[23][24][25][26][27]. Graphene with its inherent tunability is a good candidate for reconfigurable and intelligent multi-beam nano-antennas because of its high conductivity and little skin effect in THz spectrum and high absorptive feature in visible and near-infrared spectra [25,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, multi-beam reconfigurable plasmonic nano-antennas based on graphene have attracted tremendous attention due to the unique features of graphene as a promising two-dimensional (2D) monoatomic layer of carbon atoms in optical and terahertz (THz) frequency range for electronic and photonic applications [3,[23][24][25][26][27]. Graphene with its inherent tunability is a good candidate for reconfigurable and intelligent multi-beam nano-antennas because of its high conductivity and little skin effect in THz spectrum and high absorptive feature in visible and near-infrared spectra [25,28].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, graphene-based reconfigurable THz antennas have been widely investigated [29][30][31], but limited studies have been done on graphene-based nano-antennas especially graphene HPWAs for operating at telecommunication wavelengths. In [24] a smart multi-beam cross-dipole nano-antenna has been proposed and shown that by applying different chemical potentials of graphene at the wavelength of 1550 nm the direction of radiation pattern can be controlled easily due to the absorptive and transparent specifications of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…The referred-to electromagnetic resonances are called surface plasmon polaritons (SPP). The surface plasmon polaritons are related to the transition of electrons in the energy band [21]. The phenomenon results in the diffusion of intense light and increased absorption of a localized electromagnetic field [22].…”
Section: Plasmonic Nanoantennamentioning
confidence: 99%
“…With recent technological advances, it is now possible to establish nanodevices and subwavelength structures with adequate precision. These nanostructures can include nanoantennas, plasmonic devices, metamaterials, and terahertz filters 2 , 3 . Plasmonic devices direct and control light at a metal/dielectric interface.…”
Section: Introductionmentioning
confidence: 99%